The Moderating Effect of Stakeholders Management on the Relationship Between Organizational Characteristics and Performance of African Ports - Atonga, J.O.; Awino, Z.B.; Ogollah, K.; Odock, S.O. (European Scientific Journal, ESJ, 2024)
The main objective of this study was to determine the moderating effect of stakeholders’ management on the relationship between organizational characteristics and the performance of seaports in Anglophone Africa. This study adopted a positivist research philosophy with a descriptive cross-sectional census survey design. Structured questionnaires were employed to collect primary data targeting executive managers of container-handling seaport terminals in Africa who are knowledgeable in port operations and management. Additional published data was also obtained from the websites of some of the ports. The response rate was 83.6%. The reliability and validity of the indicator items were ascertained through diagnostic tests. The use of SRMR and NFI confirmed model fitness. Partial Least Squares Structural Equation Modeling using Smartpls 4.0 software was used for data analysis and measurement model estimation to test the null hypothesis that there is no significant moderating effect of stakeholders’ management on the relationship between organizational characteristics and the performance of seaports in Africa. The finding established a positive and significant moderating effect of stakeholders’ management on the relationship. The study concluded that sound and competent stakeholders’ management enhances port container terminal performance thereby creating a competitive advantage for ports in Anglophone Africa. The study adds to new knowledge, theory, policy, and practice by recommending that seaports in Africa should mitigate possible conflicts from stakeholders while developing new ports or expanding existing ports by embracing stakeholder theory.